HUBUNGAN ANTARA TINGKAT PENDIDIKAN DENGAN PEMILIHAN ALAT KONTRASEPSI PADA PASANGAN USIA SUBUR DI DESA KRAKAL (Edu Geography, 2016)
This study aims to determine is there a relationship between level of education and elections in the village Krakal contraceptives and contraceptive or birth control widely used type of couple of childbearing age. The method used in the form of a quantitative approach to biserial correlation analysis. The results showed a strong correlation between education level with the election of contraception on couple of childbearing in Krakal village of 15,0, the majority of couple of childbearing age graduating junior by 56% and the majority use injections. Couple od childbearing reason do injections as effective in preventing pregnancy, safe, low fees and minimal side effects. Health infrastructure in the village Krakal still need to be improved such as: hours of practice is extended until the afternoon, a pediatrician and the content needs to be provided.